Mathematical Modelling of Nitric Oxide Release Caused by Exocytosis and Determination of a Stellate Neuron Activity Function in Rat Brain - Oleinick, A.; Amatore, C.; Klymenko, O.; Svir, I. (Nonlinear Analysis: Modelling and Control, 2007)
In this work we report the results of the mathematical modelling of NO◦ -release by neurons considering a series of Gaussian bursts, together with its transport in the brain by diffusion. Our analysis relies on the NO◦ -release from a neuron monitored before, during and after its patch-clamp stimulation as detected by an ultramicroelectrode introduced into a slice of living rat’s brain. The parameters of the neuron activity function have been obtained by numerical fitting of experimental data with simulated theoretical results. Within our initial hypothesis about the Gaussian decomposition of NO◦ -release that allowed drawing qualitative and quantitative conclusions about the considered neuron activity function. It is noted that since the activity function can be readily modified this signal processing may be adapted to the treatment of other and maybe more physiologically relevant hypotheses.
Keywords: brain slice; neuron activity function; nitric oxide release; Gaussian decomposition; conformal mapping; numerical fitting